The Springtime of the People: The Athenian Ephebeia and Citizen Training from Lykourgos to Augustus - Henderson, Thomas R. (Brill Studies in Greek and Roman Epigraphy, 2020)
In The Springtime of the People: The Athenian Ephebeia and Citizen Training from Lykourgos to Augustus Thomas R. Henderson provides a new history of the Athenian ephebeia, a system of military, athletic, and moral instruction for new Athenian citizens. Characterized as a system of hoplite training with roots in ancient initiation rituals, the institution appears here as a later Lykourgan creation with the aim of reinvigorating Athenian civic culture. This book also presents a re-evaluation of the Hellenistic phase of the ephebeia, which has been commonly regarded as an institution in decline. Utilizing new epigraphic material, the author demonstrates that, in addition to rigorous military training, the ephebeia remained an important institution and played a vital and vibrant part of Athenian civic life.